2007
DOI: 10.1002/hep.21596
|View full text |Cite
|
Sign up to set email alerts
|

Novel liver‐specific organic anion transporter OAT7 that operates the exchange of sulfate conjugates for short chain fatty acid butyrate†

Abstract: The liver plays an important role in the elimination of endogenous and exogenous lipophilic organic compounds from the body, which is mediated by various carrier proteins that differ in substrate specificity and kinetic properties. Here, we have characterized a novel member of the organic anion transporter family (SLC22) isolated from human liver. The transporter named organic anion transporter 7 (OAT7/ SLC22A9) showed 35% to 46% identities to those of other organic anion transporters of SLC22 family. When exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
113
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(116 citation statements)
references
References 47 publications
2
113
0
1
Order By: Relevance
“…Similar results were observed in OAT7. As we reported, OAT7-mediated estrone sulfate transport was inhibited by 3-to 5-carbon SCFAs, but only butyrate was transported by OAT7 (3). In that case, we suggested that propionate and valerate bind to the substrate binding site of OAT7 but they are not translocated by OAT7.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Similar results were observed in OAT7. As we reported, OAT7-mediated estrone sulfate transport was inhibited by 3-to 5-carbon SCFAs, but only butyrate was transported by OAT7 (3). In that case, we suggested that propionate and valerate bind to the substrate binding site of OAT7 but they are not translocated by OAT7.…”
supporting
confidence: 60%
“…Just recently, we have demonstrated that a novel liverspecific organic anion transporter OAT7 transports organic anion in exchange for a short-chain fatty acid (SCFA) butyrate at the sinusoidal membrane of hepatocytes and suggested that OAT7 functions as an entrance pathway for butyrate (3). SCFAs such as butyrate are generated at high levels in the colon, absorbed into colonic epithelial cells, and largely removed by these cells (9).…”
mentioning
confidence: 99%
“…Meanwhile, nine OATs were functionally identified (OAT1, OAT2 (8), OAT3 (9), OAT4 (10), Oat5 (11), Oat6 (12), OAT7 (13), Oat v 1 (14), and the urate transporter URAT1 (15)). Most of these are highly expressed in the kidneys (OAT1-OAT4, Oat5, Oat v 1, and URAT1), whereas Oat6 is only expressed in the olfactory bulb, and the recently identified human OAT7 is currently the only liver-specific OAT.…”
mentioning
confidence: 99%
“…OATS 5-10 are relatively less explored compared to the OATs above mentioned. OAT5 and OAT7 are expressed in human liver, while OAT10 were found in the apical membrane of proximal tubules cells [21][22][23]. Minimal information is available for these OATs, in particular, their genetic polymorphisms.…”
Section: Transporter Function and Tssue Distribution Of Oatsmentioning
confidence: 99%